(untitled) (Indian Journal of Public Health Research & Development, 2020)
Self esteem is the expression of the existence of psychological health. Self esteem is needed as it is one of the most important human rights. Self esteem is greatly affects the quality of life as well as the productivity of the people that is why the self esteem is greatly impacted on the student’s performance as they are the future of our country. This study has conducted to assess the existing level of self esteem among east Midnapore college students of technical and allied stream; also it is concentrated on whether self esteem is significantly related with gender of the students and area the students are residing. Total 159 students are included in the study after doing convenient sampling method. A questionnaire has formed which follows Rosenberg Self Esteem scale system. T test and ANOVA has conducted by SPSS 21 software and it shows neither gender nor area are significantly related with the level of self esteem among students of technical and allied stream because in every cases the p value is greater than .05.